Analysis of 5S rDNA Genomic Organization Through the RepeatExplorer2 Pipeline: A Simplified Protocol - Garcia, Sònia; Pascual-Díaz, Joan Pere; Krumpolcová, Alice; Kovarík, Ales (Methods in molecular biology (Clifton, N.J.), 2023)
The ribosomal RNA genes (rDNA) are universal genome components with a housekeeping function, given the crucial role of ribosomal RNA in the synthesis of ribosomes and thus for life-on-Earth. Therefore, their genomic organization is of considerable interest for biologists, in general. Ribosomal RNA genes have also been largely used to establish phylogenetic relationships, and to identify allopolyploid or homoploid hybridization.Here, we demonstrate how high-throughput sequencing data, through graph clustering implemented in RepeatExplorer2 pipeline ( https://repeatexplorer-elixir.cerit-sc.cz/galaxy/ ), can be helpful to decipher the genomic organization of 5S rRNA genes. We show that the linear shapes of cluster graphs are reminiscent to the linked organization of 5S and 35S rDNA (L-type arrangement) while the circular graphs correspond to their separate arrangement (S-type). We further present a simplified protocol based on the paper by (Garcia et al., Front Plant Sci 11:41, 2020) about the use of graph clustering of 5S rDNA homoeologs (S-type) to identify hybridization events in the species history. We found that the graph complexity (i.e., graph circularity in this case) is related to ploidy and genome complexity, with diploids typically showing circular-shaped graphs while allopolyploids and other interspecific hybrids display more complex graphs, with usually two or more interconnected loops representing intergenic spacers. When a three-genomic comparative clustering analysis from a given hybrid (homoploid/allopolyploid) and its putative progenitor species (diploids) is performed, it is possible to identify the corresponding homoeologous 5S rRNA gene families, and to elucidate the contribution of each putative parental genome to the 5S rDNA pool of the hybrid. Thus, the analysis of 5S rDNA cluster graphs by RepeatExplorer, together with information coming from other sources (e.g., morphology, cytogenetics) is a complementary approach for the determination of allopolyploid or homoploid hybridization and even ancient introgression events.
Keywords: RNA ribozomální 5S; Phylogeny; RNA, Ribosomal, 5S; geny rRNA; Allopolyploid hybridization; Genes, rRNA; 5S ribosomal RNA genes; Homoploid hybridization; fylogeneze; Graph clustering; genomika; Genomics; Genomic analysis; DNA, Ribosomal; ribozomální DNA; Introgression; Repeatome